Pengembangan Aplikasi Taman Hiburan Berbasis Android - Bagas Andaryanto; Fajar Pradana; Achmad Arwan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
This research is done based on a problem that we can easily found in real life that we are often making a transaction manually. The tourist will find that doing manual transaction while on a vacation will be very difficult, it is hard to control the flow of our money without making any note for it. The other problem is, the tourist are sometimes got confused to determine a place for a vacation. The solution of this problem is a cashless payment system. With a cashless payment, it will allow you to at least know where your money went and how much you spend while you are on a vacation. In addition, the sellers also doesnt need to bother look for some change. In this study there is 3 case studies that have the same business prosess. Not only that, this research will also give a tourist an excact location of them and will lead them to a certain place on a amusement park, that will reduce the potential of getting lost. This system is having an android operating system in a mobile device. The system testing in this system is unit testing and integration testing using a whitebox testing method and the other one is validation testing which resulting a 100% valid value for all test cases using a blackbox testing method.